Hak Konsumen dalam Penyiaran Televisi - Wardah Wardah (Universitas Syiah Kuala, 2014)
The development of business in television services have been fastly growing in the recent years. On one hand, it gives more attractive an programs for viewers, brings variative means to promote products for bussiness people, and also generates incomes for the TV station owners from adverstisemens.On the other hand, it also brings negative impacts on spectators. It is needed the knowledge for the viewers to choose the good programs to watch. The Government of Indonesia has legalized the Law No. 32/2002 on Broadcasting in order to protect and guarantee the consumer’s rights. The Consumer’s Rights on TV Broadcasting